2017
DOI: 10.18632/oncotarget.16996
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of LMP1-expressing cells from a monolayer of gastric cancer AGS cells

Abstract: Epstein-Barr virus (EBV) latently infects malignant epithelial cells in approximately 10% of all gastric cancers. Latent membrane protein 1 (LMP1), an oncogenic protein, plays an important role in malignant transformation in EBV-associated nasopharyngeal carcinoma and B-cell lymphoma; however, its expression has not been detected in EBV-associated gastric cancer. To address why LMP1 has not been detected in EBV-positive gastric tumors, we focused on the interactions between LMP1-positive and -negative cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Accumulating evidence shows the abortive lytic cycle as a third state of EBV infection occurring in the pre-latent phase of EBV primary infection ( Wen et al, 2007 ; Kalla et al, 2010 ; Jochum et al, 2012a , b ; Sato et al, 2017 ; Wang et al, 2019 ) and within EBV-associated tumors ( Hong et al, 2005 , 2009 ; Murata et al, 2019 ; Okuno et al, 2019 ). In this state, the full lytic program is not induced due to an incomplete expression cascade of viral lytic genes; thus, infectious particles are not produced.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence shows the abortive lytic cycle as a third state of EBV infection occurring in the pre-latent phase of EBV primary infection ( Wen et al, 2007 ; Kalla et al, 2010 ; Jochum et al, 2012a , b ; Sato et al, 2017 ; Wang et al, 2019 ) and within EBV-associated tumors ( Hong et al, 2005 , 2009 ; Murata et al, 2019 ; Okuno et al, 2019 ). In this state, the full lytic program is not induced due to an incomplete expression cascade of viral lytic genes; thus, infectious particles are not produced.…”
Section: Introductionmentioning
confidence: 99%
“…Although LMP1 plays a crucial role in EBV-mediated malignancies, LMP1 has seldom been detected in EBV-positive gastric tumors. A study by Sato et al ( 2017 ) provides a hint toward the mechanism explaining this controversial observation. They demonstrated that co-culture of LMP1-positive and -negative gastric cancer cells leads to elimination of LMP1-positive cells, through the release of LMP1-loaded exosomes that mediate epidermal growth factor receptor (EGFR) activation in LMP1-negative cells.…”
Section: Exosomesmentioning
confidence: 99%
“…Growth curves were measured as described previously [14]. Briefly, Akata(-) cells were seeded at a density of 1 × 10 5 cells/mL.…”
Section: Methodsmentioning
confidence: 99%
“…The amount of virus particles in the culture supernatant and the number of infected cells were routinely measured as follows: a portion (400 μL) of the infected cell culture was routinely harvested, and the amount of released infectious virions in the culture supernatant was quantified as described previously [46]. The cell number was counted as described previously [14]. The percentage of infected cells was quantified by FACS [46].…”
Section: Methodsmentioning
confidence: 99%